Corrección de “Patients´ and Therapists´ Reports of Psychotherapy Outcomes: Similarities and Differences” [Psicothema 35(4), 374-384] - Fernández-Rodríguez, Concepción; Martínez-Loredo, Víctor; Coto-Lesmes, Rocío (Psicothema, 2024)
Sin resumen